Contact lens use and practice among health sciences and business management students: a survey / Nur Aresya Ahmad Najmee and Raihana Athira Roszili - Ahmad Najmee, Nur Aresya; Roszili, Raihana Athira (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
This qualitative study aimed to determine the practices in contact lens use and care among contact lenses wearers from Health Sciences and Business Management students. Participants were required to answer the electronic questionnaire regarding the contact lens care regimen and practices in daily life. The behavior of wearing lenses longer than 12 hours and routine of using enzyme remover tablet in both groups showed significant result (H: 5.7%, B: 21.4%, p = 0.03) and (H: 25.7%, B: 50.0%, p = 0.04) respectively. The common improper behaviors of lens care were similar in both groups, including wearing lenses longer than recommended, not changing the lens storage solution daily, and not washing hands before handling lenses. Health Sciences students had better knowledge and behavior of contact lens care than Business Management students. However, both groups were still lacked in care knowledge and did not practice the proper contact lens use. Therefore, to prevent contact lens-related complications, awareness of the good practices in contact lens use is warranted to all contact lens wearers, regardless of formal study areas.